+0  
 
0
62
1
avatar

How do I prove Cramer's Rule? 

 

 

[Example of Cramer's]

 

ax+by=e, 

cx+dy=f

Cramer's Rule states that if \(\begin{bmatrix} a && b \\ c && d \end{bmatrix}\) is nonzero, then the solution to the system [left above] is x =  \(\begin{bmatrix} e && b \\ f && d \end{bmatrix} \over \begin{bmatrix} a && b\\ c && d \end{bmatrix}\) and y = \(\begin{bmatrix} a && e \\ c && f \end{bmatrix} \over \begin{bmatrix} a && b \\ c && d \end{bmatrix}\)

 

How Cramer's Rule works:  \(\begin{bmatrix} a && b \\ c && d \end{bmatrix}\)  = ad - bc

 Feb 16, 2022
 #1
avatar+23183 
+2

ax + by  =  e   --->   · d   --->     adx + bdy  =  de

cx + dy  =  f    --->   · -b   --->   -bcx - bdy  =  -bf

                                       --->     (ad - bc)x  =  (de - bf)

                                       --->                  x  =  (de - bf) / (ad - bc)

 

ax + by  =  e   --->   ·-c   --->     -acx -  bcy  =  -ce

cx + dy  =  f    --->   · a   --->      acx + ady  =   af

                                       --->     (ad - bc)y  =  (af - ce)

                                       --->                  x  =  (af - ce) / (ad - bc)

 

which match the solutions that you get when you use Cramer's formula.

 Feb 16, 2022

22 Online Users